APPLICATION OF NORMS ON THE ENCOURAGEMENT OF PUBLIC CIVIL SERVANTS AS A BASIS FOR PUBLIC EXPENSES - Victoria V. Volkova (Russian Studies in Law and Politics)
The changes taking place today in the legal policy of the state, including issues of organization of the state civil service, are directly related to the need to meet the existing trends in the development of the life of the state of society. This is directly related to the increasing role of the policy of incentives for public civil servants. The issue of encouragement of civil servants in Russia is regulated by a multitude of normative legal acts, which are the basis for public expenditures. In addition, they also contain measures aimed at optimizing expenditures and increasing the transparency of the incentive process. The problem of encouragement of public civil servants will always be relevant for the reason that it is designed to ensure the most effective use of personnel. The current system of incentives for public civil servants in Russia has some shortcomings that need to be corrected. In particular, it is important to form such a system of incentives for public civil servants that will be able to ensure the most effective fulfillment of their official duties. In order to retain the most qualified personnel, it is necessary to provide state civil servants with the opportunity to move up the career ladder with a decent list of rewards for the conscientious fulfillment of their official duties. All this plays an important role in creating an effective state apparatus that can best serve the public and state interests.